The Response of Clamped Shallow Sandwich Arches with Metallic Foam Cores to Projectile Impact Loading - Yanping Fan (Latin American Journal of Solids and Structures)
Abstract The dynamic response and energy absorption capabilities of clamped shallow sandwich arches with aluminum foam core were numerically investigated by impacting the arches at mid-span with metallic foam projectiles. The typical deformation modes, deflection response, and core compression of sandwich arches obtained from the tests were used to validate the computation model. The resistance to impact loading was quantified by the permanent transverse deflection at mid-span of the arches as a function of projectile momentum. The sandwich arches have a higher shock resistance than the monolithic arches of equal mass, and shock resistance could be significantly enhanced by optimizing geometrical configurations. Meanwhile, decreasing the face-sheet thickness and curvature radius could enhance the energy absorption capability of the sandwich arches. Finite element calculations indicated that the ratio of loading time to structural response time ranged from 0.1 to 0.4. The projectile momentum, which was solely used to quantify the structural response of sandwich arches, was insufficient. These findings could provide guidance in conducting further theoretical studies and producing the optimal design of metallic sandwich structures subjected to impact loading.